2010
DOI: 10.1007/s10681-010-0243-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grafting on cold responsive gene expression in Satsuma mandarin (Citrus unshiu)

Abstract: The major limitation preventing the expansion of Satsuma mandarin (Citrus unshiu) production in the Gulf Coast regions of the US is the risk of freeze damage. Poncirus trifoliata (L.) Raf has been widely used as a cold hardy rootstock for citrus production in freeze-prone environments. In this study, relative quantitative real-time RT-PCR was used to study cold responsive genes in Satsuma mandarin (C. unshiu), C. unshiu grafted on P. trifoliata rootstock and P. trifoliata following exposure to cold shock or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…Very high transcript levels of nitrate transporter (431 fold increase) were observed in Poncirus , a cold hardy rootstock for citrus. While much lower levels were observed in Satsuma mandarin [62]. Higher transcription level of nitrate transporter gene indicates the possible role in nitrate acquisition in cold-hardness V. amurensis .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Very high transcript levels of nitrate transporter (431 fold increase) were observed in Poncirus , a cold hardy rootstock for citrus. While much lower levels were observed in Satsuma mandarin [62]. Higher transcription level of nitrate transporter gene indicates the possible role in nitrate acquisition in cold-hardness V. amurensis .…”
Section: Discussionmentioning
confidence: 81%
“…The expression of a nitrate transporter gene NRT2 (At1g08090) was induced by cold, mannitol and NaCl treatment in the root of Arabidopsis [61]. Species specific expression differences of nitrate transporter were observed in citrus upon exposure to 4°C [62]. Very high transcript levels of nitrate transporter (431 fold increase) were observed in Poncirus , a cold hardy rootstock for citrus.…”
Section: Discussionmentioning
confidence: 99%
“…Duncan) and positively correlated with flavonoids biosynthesis [35]. The UGT708G1 from kumquat (Fortunella crassifolia) and UGT708G2 from satsuma mandarin (Citrus unshiu) are involved in flavonoids accumulation [36] and regulates the anthocyanin pigments biosynthesis [37] and in citrus UGTs genes respond to different environmental conditions [51,52]. To the author's knowledge, this study provided an evidence of UGT78D3s' function in both anthocyanins and proanthocyanidins.…”
Section: Discussionmentioning
confidence: 75%
“…All cold, drought, and salt stresses also stimulate the accumulation of compatible osmolytes and antioxidants (Hasegawa et al, 2000). Huang et al (2011) reported that accumulation of anthocyanin was enhanced by cold stress, and that transcript levels of CHI were dependent on interspecific backgrounds being elevated to much higher levels in Poncirus rootstock during cold acclimation. PAL and CHS mRNAs of Arabidopsis were accumulated coordinately in response to low temperatures in a light-dependent manner (Leyva et al, 1995).…”
Section: Resultsmentioning
confidence: 99%